2017
DOI: 10.1007/s10826-016-0633-0
|View full text |Cite
|
Sign up to set email alerts
|

It’s OK to Fail: Individual and Dyadic Regulatory Antecedents of Mastery Motivation in Preschool

Abstract: Mastery motivation is closely related to children’s regulatory processes and is socialized by parents. However, we know little about how individual child and dyadic parent-child regulatory processes work together to foster the early development of mastery motivation in preschool. The present study examined dyadic persistence in parent-child interactions, children’s effortful control, and children’s successful versus failed attempts in a challenging object mastery task at age 3.5 years and their prediction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…This approach enables researchers to identify and examine the relevance of parental and child behavioral states that occur at the same time. In a sample of preschoolers, the degree to which parent–child dyads spent more time in stable co-regulated states predicted positive teacher ratings of social skills with adults and peers (Lunkenheimer & Wang, 2017). In a previous publication with the current sample, we showed that a state space measure of positive dyadic coregulation was significantly linked to teacher reports of children’s self-regulation, whereas global ratings of the same construct were not (Bardack et al, 2017).…”
Section: The Role Of Parental Control and Scaffolding For Efs And Sel...mentioning
confidence: 99%
“…This approach enables researchers to identify and examine the relevance of parental and child behavioral states that occur at the same time. In a sample of preschoolers, the degree to which parent–child dyads spent more time in stable co-regulated states predicted positive teacher ratings of social skills with adults and peers (Lunkenheimer & Wang, 2017). In a previous publication with the current sample, we showed that a state space measure of positive dyadic coregulation was significantly linked to teacher reports of children’s self-regulation, whereas global ratings of the same construct were not (Bardack et al, 2017).…”
Section: The Role Of Parental Control and Scaffolding For Efs And Sel...mentioning
confidence: 99%
“…As such, to narrow in on persistence in specific circumstances, researchers have employed behavioral measures including novel puzzles or trivia games to observe children's approaches to challenge (Smiley & Dweck, 1994). In these assessments, duration of time spent on task or number of failed attempts serve as measures of task persistence (Berhenke et al, 2011;Chang & Burns, 2005;Lunkenheimer & Wang, 2017;Mokrova et al, 2013). Using these methods, researchers have found that preschool children's persistence on a challenging puzzle task predicted behavioral assessment scores (Lunkenheimer & Wang, 2017) and teacher ratings of self-regulation (Berhenke et al, 2011), as well as performance on standardized measures of math, literacy, and language proficiency (Mokrova et al, 2013).…”
Section: Task Persistencementioning
confidence: 99%
“…In these assessments, duration of time spent on task or number of failed attempts serve as measures of task persistence (Berhenke et al, 2011;Chang & Burns, 2005;Lunkenheimer & Wang, 2017;Mokrova et al, 2013). Using these methods, researchers have found that preschool children's persistence on a challenging puzzle task predicted behavioral assessment scores (Lunkenheimer & Wang, 2017) and teacher ratings of self-regulation (Berhenke et al, 2011), as well as performance on standardized measures of math, literacy, and language proficiency (Mokrova et al, 2013). Combined, these finding suggests that duration of persistence is a valid indicator of a child's early adaptive approach to learning and that longer engagement with a challenging, but achievable task benefits acquisition of academic material.…”
Section: Task Persistencementioning
confidence: 99%
See 2 more Smart Citations